دور الانتاج الأنظف في تحقيق فعالية الأداء البيئي للمؤسسة - عوينة, فاطمة; جيلالي, شفيق (جامعة الوادي - University of Eloued, 2021)
ملخص: نهدف من خلال هذه الدراسة للتعرف على علاقة الانتاج الأنظف وفعالية الأداء البيئي، من خلال الوقوف على حقيقة إدماج المؤسسات الجزائرية للبعد البئي في استراتيجياتها، باستخدامها لمدخل الإنتاج الأنظف وتكنولوجيا الانتاج الأنظف للرفع من فعالية أدائها البيئي، وبمعرفة السلوك البيئي التي تنتهجه المؤسسات نحو تحقيق فعالية بيئية وبالتالي تحقيق أداء بيئي، ومنه تحسين الأداء الكلي للمؤسسة في ظل تنمية مستدامة. وللوصول إلى أهداف الدراسة، أخذنا عينة من المؤسسات الجزائرية من خلال استقصائها عن طريق استبيان صمم خصيصا لذلك، توصلنا من خلاله إلى أن المؤسسة الجزائرية تعتمد على مدخل الإنتاج الأنظف لتحقيق فعالية أدائها البيئي. الكلمات المفتاحية: إنتاج أنظف؛ أداء بيئي؛ فعالية بيئية. Abstract: We aim, through this study, to know the relationship of cleaner production and the effectiveness of environmental performance, by standing on the fact that Algerian enterprises incorporate the environmental dimension in their strategies, using the approach of cleaner production and cleaner production technology to increase the effectiveness of their environmental performance, and by knowing the environmental behavior that institutions pursue towards achieving environmental effectiveness. Thus achieving environmental performance, including improving the overall performance of the institution in light of sustainable development. In order to reach the objectives of the study, we took a sample of Algerian enterprises through their survey through a specially designed questionnaire, through which we concluded that the Algerian enterprise relies on the approach of cleaner production to achieve the effectiveness of its environmental performance. Key words: cleaner production; Environmental performance; environmental effectiveness.
The role of cleaner production in achieving effective environmental performance of the enterprise
مقال
Keywords: إنتاج أنظف ; أداء بيئي ; فعالية بيئية; cleaner production ; Environmental performance ; environmental effectiveness